Genetic variability studies of major yield components in segregating population derived from pistillate lines of castor (Ricinus communis L.): GENETIC VARIABILITY OF YIELD COMPONENTS IN SEGREGATING POPULATION LINES OF CASTOR - C LAVANYA; T MANJUNATHA; S SENTHILVEL; K T RAMYA (Journal of Oilseeds Research, 2022)
A segregating population was developed by crossing two pistillate (female) lines of castor viz., IPC-23 and IPC-21. Population behavior was studied to understand the variability for major yield and yield components. The distribution of node number, plant height and seed yield were deviated fromnormal distribution and it was positively skewed with significant leptokurtic curve indicating that the two parents with high seed yield were selected for population development. Positive skewness indicates that the plants with exceptionallyhigh seed yield were isolated from the population. Difference between phenotypic co-efficient of variation (PCV) and genotypic co-efficient of variation (GCV) was very low to moderate for major yield components viz., number of effective spikes per plant, number of nodes to primary spike, plant height, total spike length and effective spike length of primary indicating that phenotypic selection can be effectively used for yield improvement. High heritability and genetic advance over mean (GAM) indicated the role of additive gene action for plant height and total/effective primary spike length. Correlation of number of nodes up to the primary spike with plant height up to primary spike, and total/effective spike length was positive indicating the possibility of short-statured, early pistillate selections with long primary spikes in castor.